Animated 'worlds' - Buchan, Suzanne; Surman, David; Ward, Paul (Eastleigh : John Libbey Publishing, 2006)
- Introduction / Suzanne Buchan ##- The joyous reception: animated worlds and the romantic imagination / Rachel Kearney ##- The animated spectator: watching the Quay Brothers' 'worlds' / Suzanne Buchan ##- The strings of the marionette / Richard Weihe ##- Gesturing toward Olympia / Heather Crow ##- Literary Len: Trade Tattoo and Len Lye's link with the literary avant-garde / Miriam Harris ##- Literary theory, animation and the 'subjective correlative': defining the narrative 'world' in Brit-lit animation / Paul Wells ##- Animated fathers: representations of masculinity in The Simpsons and King of the hill / Suzanne Williams-Rautiola ##- Animated interactions: animated aesthetics and the world of the 'interactive' documentary / Paul Ward ##- New media worlds / Thomas Lamarre ##- Style, consistancy and plausibility in the Fable gameworld / David Surman ##- Final fantasies: computer graphic animation and the [dis]illusion of life / Vivian Sobchack ##- An unrecognized treasure chest: the internet as animation archive / Karin Wehn.
boek